Fabrication Of An Abdominal Computed Tomography Phantom For Evaluation Of Image Quality And Radiation Dose - Ramli, Zuraida (2020)
Recently, there are several commercially available CT phantoms designed for various applications. However, the phantom is limited to certain types of tissueequivalent materials. Therefore, there is a need to fabricate a cost-effective abdominal CT phantom that contains multi tissue-mimicking materials for image quality and radiation dose evaluation simultaneously. A 32.0 cm diameter abdominal CT phantom was fabricated using polymethyl methacrylate with five sets of cylindrical tissuemimicking materials tubes with 6.0 cm diameter and thermoluminescence dosimeters slots that attached together.